Phenotypic integration and modularity drives skull shape divergence in the Arctic fox (Vulpes lagopus) from the Commander Islands - Martín-Serra, Alberto; Nanova, Olga; Varón-Gonzalez, Ceferino; Ortega, Germán; Figueirido-Castillo, Francisco Borja (Royal Society, 2019)
Phenotypic integration and modularity influence morphological disparity and evolvability. However, studies addressing how morphological integration and modularity change for long periods of genetic isolation are scarce. Here, we investigate patterns of phenotypic integration and modularity in the skull of phenotypically and genetically distinct populations of the Artic fox (Vulpes lagopus) from the Commander Islands of the Aleutian belt (i.e. Bering and Mednyi) that were isolated ca 10 000 years by ice-free waters of the Bering sea. We use three-dimensional geometric morphometrics to quantify the strength of modularity and integration from inter-individual variation (static) and from fluctuating asymmetry (random developmental variation) in both island populations compared to the mainland population (i.e. Chu- kotka) and we investigated how changes in morphological integration and modularity affect disparity and the directionality of trait divergence. Our results indicate a decrease in morphological integration concomitant to an increase in disparity at a developmental level, from mainland to the smallest and farthest population of Mednyi. However, phenotypic integration is higher in both island populations accompanied by a reduction in disparity compared to the population of mainland at a static level. This higher integration may have favoured morphological adaptive changes towards specific feeding behaviours related to the extreme environmental settings of islands. Our study demonstrates how shifts in phenotypic integration and modularity can facilitate phenotypic evolvability at the intraspecific level that may lead to lineage divergence at macroevolutioanry scales.
Keywords: Zorros; Vulpes logopus; Commander Islands; Geometric morphometrics; Skull shape; Morphological integration